Production of Margarine from Rice Bran Oil and Palm Kernel Oil and Analysis of Physicochemical Properties - Oktaviani, Rosiana; Paramita, Vita (Vocational College of Universitas Diponegoro, 2023)
Rice bran oil is a healthy food that contains vitamins, antioxidants, and nutrients needed in the human body and is widely used in food and cosmetics. Rice bran oil in Indonesia has also not been widely utilized as a raw material for food products. Therefore, to change the economic value of rice bran oil can be used as a food product, one of which is margarine. This study aims to determine the optimum conditions for making margarine from rice bran oil and palm kernel oil. The tests carried out in this study were water content, fat content, and emulsion stability tests. In this study, margarine was made with three variables, namely the ratio of rice bran oil and palm kernel oil (80:20; 70:30), stirring time (30 minutes, 40 minutes), and margarine storage time (5 days, 10 days) which will be designed using Factorial Design method. Based on the results, the optimal margarine formula from rice bran oil and palm kernel oil is in the variable stirring time of 37 minutes and 30 seconds, oil ratio of 80:20, and storage time of 5 days. In the optimum sample, the value of fat content was 82.94 ± 0.08%, moisture content was 14.08 ± 0.14%, and emulsion stability was 91.15 ± 0.21%.